Analisis Pengaruh Hubungan Antara Uang Saku dan Literasi Keuangan dengan Perilaku Konsumsi Siswa : (Studi Kasus Pada SMAS Al-Kahfi Islamic Boarding School) - Rianti Sukma Dewi; Naufal Fiqri Akmal; Cupian Cupian; Yulistyne Kusumaningrum (Journal of New Trends in Sciences, 2025)
This study aims to analyze the influence of pocket money and Islamic financial literacy on student consumption behavior at SMAS AL-KAHFI Islamic Boarding School. The research background is based on the importance of students' understanding of personal financial management, especially in the context of pesantren based education that integrates sharia values. The research method used was quantitative with a multiple linear regression approach to test the relationship between free variables (sharia allowance and financial literacy) and bound variables (consumption behavior). The population in this study is all students of SMAS AL-KAHFI which is 675 people. A sample of 60 students was selected using the Hair et al. formula, with data collection techniques through questionnaires as primary data sources and literature studies as secondary data. Data analysis is carried out with the help of statistical software to test the validity, reliability, and significance of relationships between variables. The results of the study show that simultaneously, pocket money and Islamic financial literacy have a significant influence on students' consumption behavior. Partially, allowances have a positive and significant effect, showing that the larger the allowance received, the higher the tendency of students to consume. Meanwhile, Islamic financial literacy has a positive but insignificant effect, which indicates that understanding of Islamic finance principles has not fully affected students' consumption patterns in real terms. A determination coefficient of 85.5% indicates that both independent variables are able to explain most of the variation in students' consumption behavior, while the rest are influenced by other factors outside the model. This research contributes to the development of Islamic finance education in the pesantren based school environment and becomes the basis for wiser management of pocket money among students.